PENGARUH ROTASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING DI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN B YOGYAKARTA - Sutarto Tri Antoro; Nur Widiastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to examine the effect of employee rotation and workload on job satisfaction and employee performance, as well as test job satisfaction as a mediator in the relationship between employee rotation and workload on the performance of Yogyakarta Customs employees. Data were obtained from a survey of the entire population of Yogyakarta Customs employees as many as 102 people. A structural model using Partial Least Square (PLS) method is used for data analysis. Analysts conducted with SmartPLS software indicate that employee rotation has no effect on employee performance but has a significant effect on employee performance through job satisfaction. Meanwhile, the workload has a significant effect on employee performance either directly or through employee satisfaction. Thus, job satisfaction has a significant effect on employee performance and can mediate the relationship between employee rotation and workload on employee performance.